2019
DOI: 10.1103/physrevd.99.026005
|View full text |Cite
|
Sign up to set email alerts
|

Conformal bootstrap to Rényi entropy in 2D Liouville and super-Liouville CFTs

Abstract: The Rényi entanglement entropy (REE) of the states excited by local operators in two-dimensional irrational conformal field theories (CFTs), especially in Liouville field theory (LFT) and N = 1 super-Liouville field theory (SLFT), has been investigated. In particular, the excited states obtained by acting on the vacuum with primary operators were considered. We start from evaluating the second REE in a compact c = 1 free boson field theory at generic radius, which is an irrational CFT. Then we focus on the two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 112 publications
(257 reference statements)
0
24
0
Order By: Relevance
“…It is very interesting to compare our result to the dynamics of the reflected entropy in other CFTs, in particular, integrable CFTs. There are many works to study entanglement entropy after a local quench in various setups [4,5,52,53,71,[86][87][88][89][90][91]. Their motivation is to characterize CFT classes by the dynamics of entanglement.…”
Section: Reflected Entropy In Integrable Systemmentioning
confidence: 99%
“…It is very interesting to compare our result to the dynamics of the reflected entropy in other CFTs, in particular, integrable CFTs. There are many works to study entanglement entropy after a local quench in various setups [4,5,52,53,71,[86][87][88][89][90][91]. Their motivation is to characterize CFT classes by the dynamics of entanglement.…”
Section: Reflected Entropy In Integrable Systemmentioning
confidence: 99%
“…Moreover, the Rényi entanglement entropy has been used as a very helpful quantity to measure the properties of the vacuum state and excited states [55][56][57][58][59][60][61][62][63][64][65][66]. In the undeformed CFTs, the nth Rényi entanglement entropy S (n) A has been extensively studied in the literature [58][59][60][61][64][65][66][67][68][69][70][71][72][73][74]. In rational CFTs, it has been shown that the excess of the Rényi entanglement entropy has to be the logarithmic of quantum dimension [59] of the corresponding local operator.…”
Section: Introductionmentioning
confidence: 99%
“…As applications, we employ the formula to investigate the Rényi entanglement entropy in two-dimensional CFTs perturbatively. We just put a local primary operator following the procedure in [59][60][61][64][65][66] to obtain a locally excited state. With time evolution, the excess of Rényi entanglement entropy of deformed two-dimensional CFTs has been calculated in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both in holography and quantum field theory, these correlation functions can be also applied to obtain various interesting quantum information quantities in the deformed field theory, e.g. the Rényi entanglement entropy of local quench in various situations [63][64][65], entanglement negativity [66], entanglement purification [67], information metric [68,69], etc.…”
Section: Introductionmentioning
confidence: 99%